Mechanism-based reliability model for electronic packages - Ng, Chee Weng (2005)
Mechanism-based reliability model is different from the conventional reliability model. It is generated based on a specific failure. The failure mechanism is studied in detail to obtain a model that incorporates all significant stressing variables. For fatigue driven failure, Coffin-Manson equation is the typical and most favourable model due to its simplicity. However, important variables in thermal cycling which are dwell time and ramp rate are not considered in this model. Studies were carried out to investigate the effects of dwell time and ramp rate on the reliability of electronic packages based on Bump Limiting Metallurgy (BLM) separation failure criterion. The experimental results showed that dwell time and ramp rate significantly affected the reliability performance of the BLM structure in the electronic package. The effect of ramp rate was converted into a newly introduced variable, called effective dwell time, (tdwell)eff. Earlier failure of the BLM was observed with the increase of the (tdwell)eff and temperature change, âˆ†T. Silicon die side wall delamination (SWD) failure was studied to check the applicability of the same approach used in BLM reliability analysis to other fatigue driven failure in electronic package. The studies showed that the same approach was applicable in reliability modelling based on SWD failure. The increase of âˆ†T, dwell time and ramp rate could accelerate SWD failure.